The Challenges and Opportunities of Small-Scale Public-Private Partnership Scheme to Finance Indonesia Local Street Lighting Equipment Projects : The Case of the Madiun Regency - Maman Suhendra; Dian Handayani; Sakti Prabowo; Roihans Muhammad Iqbal (Yayasan Ilomata, 2023)
The Public-Private Partnerships Scheme (PPP) has become an important option in overcoming the gap in infrastructure financing needs. From the total number of PPP projects implemented in several countries, it was found that the number of small-scale PPP projects was relatively greater than mega PPP projects. In line with this, in the Indonesian context, regional governments are expected to be able to innovate infrastructure financing, including by using the PPP scheme. The Madiun Regency Street Lighting Equipment (APJ) PPP project is the first small-scale PPP that has completed the auction process and signed the Cooperation Agreement in Indonesia. Using the qualitative method through the relevant case study approach, this research succeeded in identifying several challenges as well as opportunities for more massive implementation potentials of small-scale PPP in APJ in the future as follows: (1) optimal risk allocations; (2) the strong commitment of the regional government as the party responsible for the cooperation project; (3) financial aspects/parameters accepted by the market; and (4) doable projects.